Synthesis and retanning performance of hollow polymer microspheres for lightweight leather processing - Nan Sun; Yang Gao; Jia-li Cheng; Xia Li; Xue-pin Liao (Collagen and Leather)
Abstract Hollow polymer microspheres (HPMs) were synthesized through emulsion polymerization for application in leather retanning, offering a novel approach to lightweight leather processing. Seed emulsion polymerization enabled the controlled synthesis of four distinct HPM sizes ranging from 300 to 650 nm. Comprehensive characterization revealed that HPMs exhibited distinct hollow structures, narrow particle size distributions, and excellent storage stabilities in emulsion form. The retanning performance of HPMs was evaluated in wet-blue. The HPMs demonstrated excellent permeation during the retanning process, selectively filling the gaps among the fibers, particularly larger spaces. The maximum thickening rate of HPM emulsion (solid content of 10%) retanned leathers reached 18.01%, surpassing the 11.32% achieved with the commercial acrylic resin retanning agent (AR, solid content of 30%) at the same dosage. The maximum absorption of HPM (88.31%) closely approached that of AR (90.23%). Furthermore, HPM retanned leathers showed satisfying performances in physical and mechanical properties. These findings demonstrate the potential of HPMs as lightweight and highly selective filling retanning agents with excellent thickening and absorption properties, offering an attractive alternative to traditional retanning agents. Graphical abstract